Circular economy in developed and developing countries : perspective, methods and examples - Popkova, Elena G.; Bogoviz, Aleksei V. (Emerald Publishing Limited, 2020)
Circular Economy in Developed and Developing Countries: Perspective, Methods And Examples discusses practical examples of formation of circular economy in the developed and developing world. Special attention is paid to the experiences of modern Russia in formation of circular economy, as Russia holds a unique position in the system of international classification of countries of the world, possessing the features of developed and developing economies. The authors seek the goal of helping develop a new approach to research, founded on the idea that ecological crisis is proof of the necessity for formation of circular economy. Methods of formation are offered based on the determined peculiarities and common regularities, where imbalance of developed and developing countries is overcome and the threat to ecological crises is reduced. Aimed at academics of world economics, circular economy and macro-economics, Circular Economy in Developed and Developing Countries provides development of the theory and methodology, as well as the practice for understanding circular economy formation.